KATEGORI PENGAMBILAN KEPUTUSAN KELUARGA MELALUIEKSPLORASI PENGAMBILAN KEPUTUSAN KELUARGA BERDASARKAN JENJANG KELAS SOSIAL - Wina Christina; Indarini . (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2011)
Seeing great opportunity of marketing products and services to family, this study explore consumer decision making that covers five social range from upper to the lowest social class. The findings of the research have proven the movement of decision making dominance in the family and depict behaviors of decision maker in each social class regarding specific product characteristics.